Multiscale simulation methods for nanomaterials - Ross, Richard B., 1958-; Mohanty, Sanat S. (Wiley-Interscience, 2008)
Explores the impact of using an arsenal of molecular modelling tools for various simulations in industrial settings. This book provides an overview of the methods for providing atomistic simulation of a range of materials using our understanding of molecular scale, nanoscale, mesoscale, and macroscale phenomena.